A Facile Fabrication of High Toughness Poly(lactic Acid) via Reactive Extrusion with Poly(butylene Succinate) and Ethylene-Methyl Acrylate-Glycidyl Methacrylate - Xue, Bin (Polymers (Basel), 2018)
As is an excellent bio-based polymer material, poly(lactic acid) (PLA)’s brittle nature greatly restricts its extensive applications. Herein, poly(butylene succinate) (PBS) was introduced to toughening PLA by melt blending using a self-made triple screw extruder through in situ reactive with ethylene-methyl acrylate-glycidyl methacrylate (EGMA). The effect of EGMA concentrations on the mechanical properties, morphology, interfacial compatibility of PLA/PBS blends were studied. Fourier transform infrared (FT-IR) results demonstrated that the epoxy group of EGMA reacts with the hydroxyl groups of PLA and PBS, which proved the occurrence of interfacial reactions among the tri-component. The significantly improved compatibility between PLA and PBS after EGMA incorporation was made evident by scanning electron microscope (SEM) characterization results. Meanwhile, the contact angle test predicted that the EGMA was selectively localized at the interface between PLA and PBS, and the result was verified by morphological analysis of cryofracture and etched samples. The EGMA improves the compatibility of PLA/PBS blends, and consequently leads to a significantly increased toughness with the elongation at break occurring 83 times more when 10 wt % EGMA was introduced than neat PLA, while impact strength also enhanced by twentyfold. Ultimately, the toughening mechanism of PLA based polymers was established based on the above analysis, exploring a new way for the extensive application for degradable material.